Artemether–lumefantrine and dihydroartemisinin–piperaquine treatment outcomes among children infected with uncomplicated Plasmodium falciparum malaria in Mwanza, Tanzania - Karol J. Marwa (BMC, 2021)
Abstract Background Artemisinin based combination therapies (ACTs) have been a cornerstone in the treatment of malaria in the world. A rapid decline in dihydroartemisinin piperaquine (DHP) and artemether lumefantrine (ALU) efficacies has been reported in some parts of South East Asia, the historical epicenter for the antimalarial drug resistance. Prolonged drug use is associated with selection of resistant parasites due to exposure to inadequate drug levels hence effects on treatment outcomes in malaria. ALU and DHP are used as first line and alternative first line, respectively, in Tanzania. This study was carried in Igombe, Tanzania to assess the efficacies of ALU and DHP in routine treatment of uncomplicated malaria among children. Methods This was a prospective study involving children up to 10 years and followed up for 28 and 35 days as per the WHO protocol, 2015 for monitoring antimalarial drug efficacy. The primary end points were crude and adjusted Adequate Clinical and Parasitological Response (ACPR), parasite clearance rate and reported adverse events. Results A total of 205 children with uncomplicated malaria were enrolled. One hundred and sixteen participants were treated with ALU, while 89 participants were treated with DHP. Two participants in the ALU group were lost within the 24 h of follow-up. The PCR unadjusted ACPR was108 (94.7%) for ALU and 88 (98.9%) for DHP, while the PCR adjusted ACPR was 109(95.6%) and 88(98.9%) for ALU and DHP, respectively, at 28 day follow-up. No treatment failure was observed in both groups. Cumulative risk of recurrent parasitemia was similar in both groups (p = 0.32). Age and parasite density were strong predictors for persistent day 1 parasitemia (p = 0.034 and 0.026, respectively). Nausea and vomiting, abdominal pain and headache were the most clinical adverse events reported in both groups of patients. Conclusion The present study shows that ALU and DHP are still efficacious after more than a decade of use with PCR corrected efficacies greater than 95% implying a failure rate less than 5% which is below the WHO minimum threshold requirement for recommendation of a change in the treatment policy. Both drugs were well tolerated with no major adverse events reported.